Tiny creatures : the world of microbes - Davies, Nicola, 1958-; Sutton, Emily (Somerville, Massachusetts : Candlewick Press, 2014)
Looks at all the different microbes that inhabit the Earth and examines the varied jobs they do.
Keywords: Microorganisms -- Juvenile literature; Microorganisms; Microorganisms